2019
DOI: 10.1088/2053-1591/ab5b4b
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable multifunctional dielectric nanocomposites based on polydimethylsiloxane mixed with metal nanoparticles

Abstract: Next generation wearable electronics require stretchable dielectrics. There has been significant effort to characterize and improve the components of dielectric composites for use in these devices. In this work, a new stretchable dielectric material, composited by silver nanoparticles (Ag NPs), nickel nanoparticles (Ni NPs), and polydimethylsiloxane (PDMS), is prepared and characterized. The alternating arrays of Ag NPs groups and Ni NPs groups in the three-dimensional matrix of PDMS function as micro capacito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Unlike conventional composites or a sole type of material, polymer-based nanocomposites may offer considerable enhancement in thermal, electrical, optical, chemical, or mechanical properties. Among them, a variety of nanostructures with highly conductive [14][15][16], dielectric [17][18][19], piezoelectric [20][21][22], triboelectric [23][24][25], photo-responsive [26][27][28], or stress-sensitive [10,[29][30][31] properties have been studied for flexible pressure sensors because of their potential in amplifying stress/strain sensing capability for human motion detection, health diagnosis, and electronic skin.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional composites or a sole type of material, polymer-based nanocomposites may offer considerable enhancement in thermal, electrical, optical, chemical, or mechanical properties. Among them, a variety of nanostructures with highly conductive [14][15][16], dielectric [17][18][19], piezoelectric [20][21][22], triboelectric [23][24][25], photo-responsive [26][27][28], or stress-sensitive [10,[29][30][31] properties have been studied for flexible pressure sensors because of their potential in amplifying stress/strain sensing capability for human motion detection, health diagnosis, and electronic skin.…”
Section: Introductionmentioning
confidence: 99%
“…10 and 11) while several studies have also demonstrated conductors with a stretchability of more than 500%, or even as high as 2000% that however have not been used to sense strain. [12][13][14][15] While a large number of previous studies have achieved a stretchability of approximately 300% and a sensitivity of approximately 50, more recent studies have found it difficult to further improve the overall strain sensor performance. [16][17][18][19][20][21][22][23][24] The use of nanomaterials and deformable structures are the two most common strategies for obtaining stretchable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Strain sensors play an important role in these fields and their performance is mainly measured by sensitivity and stretchability [9] . To date, some sensors have achieved sensitivity above 10 3 under tensile strain of less than 8% [10][11] while several studies have also demonstrated conductors with a stretchability of more than 500%, or even as high as 2000% that however have not been used to sense strain [12][13][14][15] . While a large number of previous studies have achieved a stretchability of approximately 300% and a sensitivity of approximately 50, more recent studies have found it difficult to further improve the overall strain sensor performance [16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…Rajitha and Dash proposed a PDMS/reduced graphene oxide composite that preserved optical transparency while increasing the permittivity up to 38 [ 14 ]. The addition of ceramic such as BaTiO 3 [ 15 ], SrTiO 3 [ 16 ], as well as metallic [ 17 ] nanoparticles also caused an increase in permittivity of PDMS-based composites. Moreover, on a nanometric scale, they exhibited unusual optical and electrical properties due to quantum confinement.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a remarkable enhancement of permittivity, reaching up to 900, as well as dielectric loss equal to 0.14. It was Feng et al, in turn, who proposed a composite of silver and nickel nanoparticles embedded in the PDMS matrix—a system characterized by very low dielectric loss—0.009 for 1 MHz at room temperature and a maximum dielectric permittivity of 35 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%